Myosin IXa Binds AMPAR and Regulates Synaptic Structure, LTP, and Cognitive Function - Folci, Alessandra; Murru, Luca; Vezzoli, Elena; Ponzoni, Luisa; Gerosa, Laura; Moretto, Edoardo; Longo, Fabiana; Zapata, Jonathan; Braida, Daniela; Pistillo, Francesco; Bähler, Martin; Francolini, Maura; et al. (Frontiers in Molecular Neuroscience, 2016)
Myosin IXa (Myo9a) is a motor protein that is highly expressed in the brain. However, the role of Myo9a in neurons remains unknown. Here, we investigated Myo9a function in hippocampal synapses. In rat hippocampal neurons, Myo9a localizes to the postsynaptic density (PSD) and binds the alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) GluA2 subunit. Myo9a+/- mice displayed a thicker PSD and increased levels of PSD95 and surface AMPAR expression. Furthermore, synaptic transmission, long-term potentiation (LTP) and cognitive functions were impaired in Myo9a+/- mice. Together, these results support a key role for Myo9a in controlling the molecular structure and function of hippocampal synapses.